Development of gluten-free products technology using flax flour - Gorach, Olga; Dzyundzya, Oksana; Novikova, Nataly; Rezvykh, Nina (Technology audit and production reserves, 2025)
The object of research is the production of gluten-free products. 4 samples of dough and finished products with different ratios of corn, rice and flax flour were studied. Organoleptic analysis showed that compared to the assessment of the control sample (4.7 points), sample No. 3 (4.9 points) with a ratio of corn, rice and flax flour 60:20:20 (experiment 3) is rational. Europe and other countries of the world are showing increased interest in the implementation of innovative technologies for the production of special and functional food products. Therefore, the current task is to introduce new technologies and functional formulations into production, taking into account the needs of today, aimed at preserving and increasing the biological value of food products. It was found that the physical and chemical indicators of the finished gluten-free bakery product in terms of porosity, acidity, and crumb moisture exceed the control sample. The results of the studies show that an increase in the amount of rice and flax flour leads to an increase in dough porosity by 2 % compared to the control sample. The acidity of the dough increased from 2.70 degrees to 3.1 degrees and exceeded the control sample by 0.3 degrees. The dimensional stability is almost the same as that of the control sample. The specific volume compared to the control increased by 20 cm3/100 g and amounted to 268 cm3/100 g. Based on the research results, a basic technological scheme of production has been developed and substantiated, parameters and modes of the technological process have been given. The possibility of creating functional technologies and recipes not only with high sensory, physicochemical quality indicators, but also with high nutritional value has been confirmed. This is achieved due to the content of vegetable proteins, unsaturated fatty acids and dietary fiber, minerals and vitamins in flax flour, which have a positive effect on lipid metabolism.